The impact of varying nutrient concentrations on the growth and size distributions of phytoplankton populations within the western equatorial Pacific - Smith, Sevrin (My University, 2023)
The purpose of this research is to identify how the surface water properties and population makeup of phytoplankton communities impact how their growth and size distributions respond to variations in nutrient concentrations. I conducted my research from 5 °N to 5 °S within the western Pacific during the March-February 2023 transition from La Nina to El Nino. Model nutrient data and surface water chlorophyll concentrations were used to provide context on how this transition in conditions impacted phytoplankton populations at different locations and timepoints. North to south trends along the transect displayed lower surface water chlorophyll concentrations and deeper mixed layers which is a clear indicator of changing surface water conditions. To gauge how varying nutrient additions impacted the size distributions and growth of phytoplankton populations I conducted incubation experiments on communities retrieved from the northernmost, equatorial, and southernmost station. The treatment groups I used in these experiments were a control group, a deepwater addition group, a deepwater addition paired with a silica addition group, and a deepwater addition paired with a nitrate addition group. Most of the treatment groups and size classes within the northernmost and equatorial station showed significant growth whereas the southernmost station exhibited far less growth. In contrast to the other stations, the southernmost station displayed a surprising lack of growth when exposed to higher nutrients. For the equatorial and northernmost stations, deepwater additions demonstrated the highest impact on phytoplankton growth within each of the nutrient addition groups. Overall, communities from the three locations of study showed a diverse response to changing nutrient conditions in terms of growth and shifting population size distributions.
Keywords: phytoplankton; Western Equatorial Pacific